2019
DOI: 10.14527/pegegog.2019.040
|View full text |Cite
|
Sign up to set email alerts
|

Technology-supported global education: A mixed method study

Abstract: The purpose of this study was to investigate the effects of using communication technologies in teaching of attainments related to global education in social studies course on students’ academic success, knowledge retention and their opinions on teaching practice. The research was carried out on the 6th grade students in a secondary school in the province of Samsun. In the research, exploratory order model, one of the mixed method research designs, was used. There were 44 students in the experimental group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Many studies are devoted to the effectiveness of modern technologies in education and the impact of these technologies on people's future lives. In a study by Turkish scholars on the impact of the use of communication technologies in teaching, it is noted that "the training program with technological support used in the experimental group is more effective in increasing student achievement and maintaining learning compared to a study group application that is not supported by communication technology and where teaching was teacher-oriented -a direct expression method" [2]. A study by other Turkish scholars notes that "mobile learning, science education, science education, and e-learning were the most frequently used keywords in articles over the past six years" [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies are devoted to the effectiveness of modern technologies in education and the impact of these technologies on people's future lives. In a study by Turkish scholars on the impact of the use of communication technologies in teaching, it is noted that "the training program with technological support used in the experimental group is more effective in increasing student achievement and maintaining learning compared to a study group application that is not supported by communication technology and where teaching was teacher-oriented -a direct expression method" [2]. A study by other Turkish scholars notes that "mobile learning, science education, science education, and e-learning were the most frequently used keywords in articles over the past six years" [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Belgian scholars, "in digital learning, educational support consists of two factors: information support and process management." At the same time, they found that "leadership of the process positively determines social participation, and information support is negatively related to social participation" [14].…”
Section: Introductionmentioning
confidence: 99%